Characterization of Escherichia coli carrying mcr-1-plasmids recovered from food animals from Argentina - Dominguez, Johana Elizabeth; Faccone, Diego; Tijet, Nathalie; Gomez, Sonia; Corso, Alejandra; Fernandez Miyakawa, Mariano Enrique; Melano, Roberto G. (Frontiers Media, 2019)
In this study, we found mcr-1.1 and mcr-1.5 genes carried by IncI2 plasmids in a subset of Escherichia coli isolates recovered from commercial broiler farms in Argentina. The comparative analysis of the sequences of these plasmids with those described in human clinical isolates suggests that this replicon-type is one of the main mcr-disseminator sources in Argentina.